ISOLASI, IDENTIFIKASI DAN SELEKSI JAMUR YANG BERPERAN SEBAGAI AGEN BIOREMEDIASI LOGAM KROM PADA KULTUR JAMUR SECARA IN VITRO - Irna Riski Kardila, - (2022)
The leather tanning industry in Sukaregang, Garut uses the chemical Chromosal B as a tanning agent. Liquid waste generated from leather tanning activities contains chromium metal and is directly discharged into river bodies without being processed first. Water pollution can be an environmental problem because chromium metal can be toxic to the environment. These problems can be corrected by bioremediation. The purpose of this study was to utilize fungi found in rhizosphere soil contaminated with chromium metal as a bioremediator agent. Isolated and identified fungi are fungi that are resistant to chromium metal. Chromium absorption and bioaccumulation tests were performed on single isolates and a consortium of fungi using Atomic Absorption Spectrophotometry (AAS). Thirteen genus found with two of them namely Rhodotorula and Saccharomyces Rhodotorula has a bioaccumulation value of 90.71%, Saccharomyces 91.07% and the consortium of Rhodotorula and Saccharomyces 90.71%.